KEMAMPUAN PEMAHAMAN KONSEP ALJABAR DITINJAU DARI METODE PROBLEM SOLVING LEARNING DAN METODE EKSPOSITORI - Rianita Simamora (STKIP Andi Matappa, 2020)
This study discusses the ability to understand algebraic concepts that are reviewed from two learning mottos, namely between problem solving learning and expository. This experimental study uses the non-equivalent posttest-only control group design because the two groups to be analyzed are different (non-equivalent). The treatment given to this sample group of research is problem solving method and others using expository method. SMA Negeri 3 Pematangsiantar class XIPA is the population selected in this study which amounted to 244 people and as a sample are students of grade XIPA-6 and XIPA-7 students selected using random sampling cluster method that has been declared normal and homogeneous. The instrument used is an essay test that amounts to 10 valid and reliable questions so that it is eligible to be used as a test instrument. This study used t-test (difference of two averages) to determine the difference between the two research data. The results of this study showed that there are significant differences in the ability to understand algebraic concepts when reviewed from problem solving learning and expository methods as found from the results of statistical tests of this study. The difference between the two methods is also shown by the percentage of students' learning completion in solving concept comprehension problems.